2021
DOI: 10.52380/ijpes.2021.8.2.430
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attitudes and Socio-demographic Factors as Predictors of Smartphone Addiction in University Students

Abstract: The aim of the study is to examine predictive effect of parental attitudes and socio-demographic variables (age, gender, time spent on smartphone, number of siblings, students’ feeling social, and parental education level) in university students’ addiction to smartphones. Participants included 670 university students whose age ranged between 18-30 years (M=21.6, SD=6.3). Smartphone Addiction Scale (SAS) and Parental Attitude Scale (PAS) and Socio-Demographic Information Form were used to collect data. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Çevik and Çelikkaleli (19) determined in their study that internet addiction mean scores of the adolescents whose mothers were "high school" graduates were significantly higher than those of the adolescents whose mothers were "illiterate" and "primary school graduates". In addition, Çiçek, Tanriverdi, Şanlı, & Buluş (22) did not reveal a significant difference between smartphone addiction and mother's education level in their study on university students. The difference between the fathers' educational levels and smartphone addiction of the adolescents was statistically significant.…”
Section: Discussionmentioning
confidence: 81%
“…Çevik and Çelikkaleli (19) determined in their study that internet addiction mean scores of the adolescents whose mothers were "high school" graduates were significantly higher than those of the adolescents whose mothers were "illiterate" and "primary school graduates". In addition, Çiçek, Tanriverdi, Şanlı, & Buluş (22) did not reveal a significant difference between smartphone addiction and mother's education level in their study on university students. The difference between the fathers' educational levels and smartphone addiction of the adolescents was statistically significant.…”
Section: Discussionmentioning
confidence: 81%
“…In the study of Çiçek, Tanriverdi, Şanlı, and Buluş, (2021), there was a negative and significant relationship between democratic and authoritarian parental attitudes and smartphone addiction in university students, while a positive and significant relationship was found between protective parental attitudes and smartphone addiction [33]. A positive and significant relationship between high levels of internet addiction and loneliness in university students was also emphasized in studies [34,35].…”
Section: Discussionmentioning
confidence: 97%
“…Regarding parents’ education level, a study claimed that the mean nomophobia score decreased according to the father’s higher educational level [ 24 ]. Furthermore, a relevant study found that parents’ educational level, the duration of smartphone use, and social feelings were significantly associated with the development of smartphone addiction [ 25 ]. Another study supported the negative associations between father’s educational attainment and smartphone addiction, loneliness, and advancement motivation.…”
Section: Introductionmentioning
confidence: 99%